Evolution of telecommunication in eastern Europe. - Kuentzel, D. (IEEE Communications magazine)
New global trends in telecommunications technology and liberalization will force dramatic changes in the national telecommunications of the East European countries. Some of them are described in this article. Mainly the technical issues of shaping telecommunication systems evolution in the region are considered. The major trends in regional telecommunication networks evolution-deregulation, new end user demands, and technological innovations are described first . Next, we deal with today's network structure. Finally, we describe the possible transformation of the network infrastructure in the near future.